Nivel de Conocimiento y medidas preventivas del Virus del Papiloma Humano en estudiantes de Economía de la Universidad Nacional de Loja durante el periodo septiembre 2024 - febrero 2025 - Tandazo Canchingre, Marlon Mathias (2025)
Human Papillomavirus (HPV) is the most prevalent sexually transmitted infection worldwide and is the primary cause of cervical cancer. Therefore, the present study aimed to determine the level of knowledge and preventive measures regarding HPV among students of the Economics Program at the National University of Loja during the period from October 2024 to March 2025. A descriptive observational study with a quantitative approach and a cross-sectional cohort design was conducted. The study population consisted of 180 students, with a final sample of 103 legally enrolled students from the first to the eighth academic semester. Before participating, informed consent was obtained, and students completed a sociodemographic questionnaire along with an assessment of their level of knowledge and preventive measures related to HPV. The results revealed that 77.91% of respondents demonstrated a high level of knowledge regarding HPV, while 29% exhibited a moderate level, and only 1.16% showed a low understanding of the subject. Regarding preventive measures, 74.4% reported practicing effective prevention strategies, whereas 25.6% displayed only basic preventive behaviors. A positive correlation was identified between knowledge levels and preventive practices, indicating that increased awareness of HPV infection influences the adoption of protection measures. Additionally, the findings suggest that older participants tend to have greater sexual education, with this trend being more pronounced among female students